Regeneration status and species diversity of major tree species under scientific forest management in Kapilbastu district, Nepal - Aryal, B.; Regmi, S.; Timilsina, S. (Banko Janakari, 2021)
In Nepal, scientific forest managementhas been practiced as an effective forest management technique to utilize forest resources sustainably. However, the program has faced many controversies such as intentional logging of only high-valued timber species like Shorearobusta. In addition, few believe this program is severely affecting the regeneration productivity and species diversity in the natural forests. In order to address these issues, we examinedthe regeneration condition and plant species diversity in the stands where scientific forest management operations were carried out. The data related to regeneration status and species diversity were collected using a systematic random sampling of the selected stands. Our results showed good regeneration conditions (Seedling >5000, Sapling>2000) in all the studied stands. The tree species community was dominated by S.robusta(Sal) followed by Schleicheraoleosa (Kusum) and Casia fistula (Rajbriksha). The value of diversity indices of different species varied significantly between felling series. The highest diversity was found in the second year felling series with the Simpsons Index of dominance value 0.6934 and the lowest species diversity was in the first year felling series with a value of 0.8448. It can be recommended that the regeneration felling practice has helped in promoting the regeneration condition and growth.